2022
DOI: 10.1186/s12859-022-04955-w
|View full text |Cite
|
Sign up to set email alerts
|

BRANEnet: embedding multilayer networks for omics data integration

Abstract: Background Gene expression is regulated at different molecular levels, including chromatin accessibility, transcription, RNA maturation, and transport. These regulatory mechanisms have strong connections with cellular metabolism. In order to study the cellular system and its functioning, omics data at each molecular level can be generated and efficiently integrated. Here, we propose BRANEnet, a novel multi-omics integration framework for multilayer heterogeneous networks. BRANEnet is an express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(52 reference statements)
0
4
1
Order By: Relevance
“…Stable associations, including inter- and intra-connections between proteome and transcriptome data, across distinct PDAC recurrences were identified. While multi-layer associations were also identified using pancreatic cancer TCGA datasets by Jagtap et al , the associations revealed in this study did not overlap with those found in this study [ 32 ]. The observed difference in associations identified could be attributable to the use of mRNA and protein data sets in this study, compared to the use of miRNA and mRNA data sets to perform network-based multi-omics integration.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Stable associations, including inter- and intra-connections between proteome and transcriptome data, across distinct PDAC recurrences were identified. While multi-layer associations were also identified using pancreatic cancer TCGA datasets by Jagtap et al , the associations revealed in this study did not overlap with those found in this study [ 32 ]. The observed difference in associations identified could be attributable to the use of mRNA and protein data sets in this study, compared to the use of miRNA and mRNA data sets to perform network-based multi-omics integration.…”
Section: Discussioncontrasting
confidence: 52%
“…The observed difference in associations identified could be attributable to the use of mRNA and protein data sets in this study, compared to the use of miRNA and mRNA data sets to perform network-based multi-omics integration. Alternatively, the difference could be due to a Spearman partial correlation threshold being used in this study compared to the use of a Pearson correlation threshold and biological a priori knowledge for important association determination and network construction [ 32 ]. Consequently, the strength of monotonic associations between features were measured using Spearman correlation as compared with linear associations using Pearson correlation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches can resolve protein interaction networks across tissues [29][30][31][32][33] and cell types by integrating molecular cell atlases [34,35] and extending our understanding of the relationship between protein and function [36][37][38]. Protein representation learning methods can predict multicellular functions across human tissues [31], design target-binding proteins [39][40][41][42] and novel protein interactions [43], and predict interactions between transcription factors and genes [37,38].…”
Section: Mainmentioning
confidence: 99%
“…These techniques aim at inferring GRNs by considering heterogeneous sources of data simultaneously [ 2 ]. Indeed, besides using gene expression data, these methods also rely on TF binding site patterns, or Chromatin Immuno-Precipitation data (e.g., [ 3 , 4 ]).…”
Section: Introductionmentioning
confidence: 99%